2017
DOI: 10.1371/journal.pone.0173767
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus suis sortase A is Ca2+ independent and is inhibited by acteoside, isoquercitrin and baicalin

Abstract: Sortase A (SrtA) has long been recognized as an ideal drug target for therapeutic agents against Gram-positive pathogens. However, the SrtA of Streptococcus suis (Ss-SrtA), an important zoonotic agent, has not been studied. In this study, the enzymatic properties of Ss-SrtA were investigated, and inhibition of Ss-SrtA by natural products was evaluated. Ss-SrtA was expressed and purified. The purified recombinant Ss-SrtA had maximal activity at pH 6.0–7.5, 45°C, and showed a Km of 6.7 μM for the hydrolysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Since sortase is considered as an ideal target for novel antivirulence drug design and development, sortase inhibition assay, as well as sortase activity assay, is very important for drug screening. 12 Here, two potent inhibitors (quercetin and curcumin 42 ) of SrtA were chosen to investigate whether the method can be used for SrtA inhibitor screening. The inhibition efficiency (IE) was determined by the following equation,…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since sortase is considered as an ideal target for novel antivirulence drug design and development, sortase inhibition assay, as well as sortase activity assay, is very important for drug screening. 12 Here, two potent inhibitors (quercetin and curcumin 42 ) of SrtA were chosen to investigate whether the method can be used for SrtA inhibitor screening. The inhibition efficiency (IE) was determined by the following equation,…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It then catalyzes the formation of an amide bond between the carboxyl group of the T and the cell wall precursor molecule lipid II, creating the LPETG-containing proteins that can promote bacteria adhere to host cells and tissues. Nowadays, drug resistance of pathogens becomes a worldwide health problem, due to excessive use and abuse of antibiotics . As a virulence-related molecule, sortase is not necessary for bacterial growth and its inhibitors exert little selective pressure on pathogens to develop drug resistance . Consequently, sortase is considered as an ideal target for novel antivirulence drug design and development and has attracted a lot of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, K111 forms a salt bridge with D180. AC has been identified as a novel SrtA inhibitor with an IC 50 value of 36.3 μM, and the endogenous SrtA activity indicates 86 % inhibition against S. aureus and 98 % against Streptococcus suis [130] . However, whether the discrepancy is associated with Ca 2+ or the salt bridge is still needed to be further elucidated.…”
Section: Anti-microorganismmentioning
confidence: 99%
“…Isoquercetin (IQ), as a monoglucoside of the most abundant natural flavonoid compound quercetin, widely exists in fruits, vegetables and cereals. Isoquercetin has antioxidant (Valentová, Vrba, Bancířová, Ulrichová, & Křen, 2014), antiviral (Chen, Xie, et al, 2017), immunomodulatory (Valentová et al, 2016) and other effects. In addition, studies have confirmed that IQ has anti‐tumor effects on several cancers including GC (Orfali et al, 2016).…”
Section: Natural Anti‐gic Angiogenic Compounds Derived From Plantsmentioning
confidence: 99%